Effect of Oatmeal as Fat Replacer on the Quality of Low Fat Goshtaba Prepared by Traditional and Machine Methods : doi: 10.5958/2581-6616.2021.00009.8 - Jalal, Heena; Salahuddin, Mir; Sofi, A. H.; Wani, S. A.; Pal , M. A.; Hussain , Arshid (Journal of Meat Science, 2022)
The effects of traditional and machine methods of preparation on the quality and acceptability of low-fat Goshtaba  formulated with 10% hydrated oatmeal as fat replacer was studied by evaluating them for physicochemical and sensory  quality. To achieve this objective, the raw emulsions were prepared by traditional (T) and machine (M) method following  the standardized processing protocols and formulations served as controls (T0 and M0) and were modified only to the  extent of addition of the 10% hydrated oatmeal as fat replacer and served as treatments (T1 and M1). The results showed  that the pH of T1 Goshtaba was higher (P
Keywords: Emulsion; Fat; Goshtaba; Machine; Replacer; Traditional; Wazwan